Again!!. Volume 8 - Kubo, Mitsurou, 1975- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2019)
"The president of Kanan High School's drama club is also its only member: Hanataka. Three years from now, Hanataka is going to be a celebrity famous for her sex appeal, but in high school she's timid, unsociable, shabby-looking, and widely disliked. Kinichiro can't help but be fascinated with her, and convinces Usami to have the ouendan cheer for the drama club's performance at the school festival. It's a new chapter for the ouendan, but is Kinichiro's "help" even welcome?"--Provided by publisher.